BIGSAS Journalist Award Ceremony 7.11.2024 (BIGSAS Journalist Award, 2024)
On 7 November 2024, the Africa Multiple Cluster of Excellence at the University of Bayreuth presented the prestigious ‘BIGSAS Journalist Award’, which honours outstanding journalistic contributions contributions to differentiated reporting on Africa in German-language print media. The 2024 award winners are Birte Mensing, Ruona Meyer and Bettina Rühl. The ceremony was moderated by Fatima Elmardiya Ahmed and Thierry Boudjekeu and accompanied by a keynote given by actor Eugene Boateng and musical acts by Sona Diabaté. For more information on the award please visit: https://www.africamultiple.uni-bayreuth.de/en/1_4-Public-engagement_-engagement1/BIGSAS-Journalist-Award/index.html